2017
DOI: 10.1021/acs.energyfuels.7b02814
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Effect of a Thermoresponsive Secundine Inhibitor on Coal Spontaneous Combustion

Abstract: When a high-water-cut physical inhibitor (HWPI) is sprayed on the coal in goaf, moisture in coal will undergo a substantial reduction under the influence of liquid flow and water evaporation, which severely weakens the inhibitory effect of the HWPI and greatly shortens its inhibitory lifetime. Therefore, this paper proposes a thermoresponsive secundine inhibitor (TSI) to solve the problem of poor water retention and short inhibitory lifetime by sealing the HWPI in thermoresponsive secundine. Before the ambient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Coal is still the main fossil energy even under the general trend of carbon neutrality. However, due to the poor thermal conductivity of coal, it easily causes heat accumulation, which evolves coal spontaneous combustion (CSC), resulting in the waste of resources. Therefore, it becomes highly necessary to study how the pore fissure characteristics do an impact on CSC from the perspective of structure …”
Section: Introductionmentioning
confidence: 99%
“…Coal is still the main fossil energy even under the general trend of carbon neutrality. However, due to the poor thermal conductivity of coal, it easily causes heat accumulation, which evolves coal spontaneous combustion (CSC), resulting in the waste of resources. Therefore, it becomes highly necessary to study how the pore fissure characteristics do an impact on CSC from the perspective of structure …”
Section: Introductionmentioning
confidence: 99%
“…With the loss of water, their inhibition efficiency is greatly decreased (Li et al, 2012b). In maintaining the high efficiency of inhibiting spontaneous coal combustion, the application of temperature sensitive materials as coating to allow the release of inhibitors at a specific temperature was investigated (Cui et al, 2017;Li et al, 2016a;Ma et al, 2016Ma et al, , 2017Qi et al, 2016). However, they did not consider the effect of diffusion and action range of inhibitors, and it was found that the covered area of coal was extremely limited after solid or liquid inhibitors were released.…”
Section: Introductionmentioning
confidence: 99%
“…The coal spontaneous combustion can only be prevented or controlled by altering the coal pile structure and external conditions, such as reducing the impacts from environment and strengthening the monitoring of cryogenic latency, through hindering the infiltration of air in the coal stockpile, evacuating the heat of the coal pile, and decreasing the temperature of the coal pile. [ 4–6 ] Research shows that reducing the oxygen circulation in coal piles is a more effective method to control spontaneous combustion of coal piles. When it has not reached the critical temperature, the coal can be rapidly cooled by physical thermal conduction.…”
Section: Introductionmentioning
confidence: 99%